Nutrient sources driving Sargassum growth in the northern tropical Atlantic: shipboard experiments simulating Amazon plume, Saharan dust, and vertical mixing - Fabio Nauer; Edén Magaña-Gallegos; Juliane B. Vasconcelos; Jan-Berend W. Stuut; Mar Fernández-Méndez; Edson Vasconcelos; Jesser F. Souza-Filho; Erik R. Zettler; Brigitta I. van Tussenbroek; Linda A. Amaral-Zettler (Marine Environmental Research, 2026)

Brazil’s science–policy effort to monitor native vegetation restoration - André L. Giles; Marina G. Freitas; Ana L. V. Espada; Pedro Constantino; Bruno S. Francisco; Silvia B. Rodrigues; Alexandre B. Sampaio; Isis F. de Freitas; Gabriela C. S. Bueno; Raquel C. A. Lacerda; R. Edson; Kirsten Silvius; et al. (Ambio, 2026)
In its early years, the UN Decade on Ecosystem Restoration has mobilized unprecedented global commitments. Yet, measuring restoration success remains contested, particularly in megadiverse countries where the absence of standardized indicators and assessment protocols often leads to subjective decisions by environmental agencies. Here, we present a core set of leading indicators developed through a pioneering Brazil-led science–policy collaboration between environmental agencies and research institutions. The indicators capture early vegetation recovery within four years and whether restoration trajectories are sustained or at risk of reversal. The initiative also establishes a framework that bridges science and policy to deliver practical monitoring tools. It offers a model for other megadiverse countries with complex governance, showing how simple, standardized indicators can translate restoration pledges into measurable results for the UN Decade.

Olfactory bulb 6-OHDA neurotoxicity as a model of early cortical dysfunction - Edson Fiorenza-Neto; Bruna B. Gattiboni; Karin Almeida; Luis F. Marqueze; Bassam F. Mogharbel; Juliana R. N. de Aguiar; Larissa C. Marques; Larissa R. Lazarini; Stephanie R. S. Carvalhal; Angelica Boldt; Ricardo C. Cunha; Katherine A. T. Carvalho; et al. (Molecular and Cellular Biochemistry, 2026)
The olfactory bulb (OB) is one of the earliest brain regions affected in neurodegenerative diseases such as Parkinson’s disease (PD). Its high metabolic rate, dopaminergic modulation, and connectivity with the cortical and limbic regions make it particularly vulnerable to early neuroinflammatory and oxidative processes. This study aimed to investigate whether the administration of 6-hydroxydopamine (6-OHDA) into the OB induces behavioral, redox, and inflammatory alterations associated with early cortical disturbances. Male Wistar rats were randomly assigned to the sham or 6-OHDA groups and underwent stereotaxic injection of the vehicle or 6-OHDA into the left OB. Behavioral performance was assessed in the open-field test 12 days after surgery, and cortical tissue was collected for biochemical and molecular analyses. Cytokines (IL-1β, IL-6, TNF-α, IL-10, IFN-γ, and MCP-1) were quantified by Luminex, redox parameters (CAT, GPx, MDA, and protein carbonyls) by spectrophotometry, and neuronal signaling proteins (c-FOS, CREB, and BDNF) by qPCR. Animals with 6-OHDA lesions exhibited decreased latency and increased time spent in the central zone of the open field, indicating altered exploratory behavior. IL-6 levels were significantly elevated, whereas IFN-γ was reduced in the cortex, while IL-1β, TNF-α, MCP-1, and IL-10 remained unchanged. The oxidative stress markers MDA and protein carbonyls were increased, while catalase and glutathione peroxidase activities showed no change. The expression of c-FOS, CREB, and BDNF was not significantly modified. These findings indicate that localized 6-OHDA administration in the OB is sufficient to elicit behavioral, inflammatory, and oxidative alterations in connected cortical regions, which may resemble early non-motor features associated with olfactory dysfunction, without representing a neurodegenerative disease-specific process.

Influence of agricultural residues on the formation of TiO2 phases: Real-time in situ X-ray diffraction monitoring in a reaction chamber - Rodrigo P. Feitosa; Johar Amin Ahmed Abdullah; Ramón R. Peña-Garcia; Maria G. Fonseca; Edson C. Silva-Filho; Santiago Medina-Carrasco; Maria del Mar Orta Cuevas; Josy A. Osajima (Chemical Engineering Journal, 2026)

Design and Evaluation of the Antibacterial Peptide FK18: a Therapeutic Approach for Mastitis in Dairy Animals - Tamaeh Monteiro-Alfredo; Camila de O. Gutierrez; Claudiane V. Almeida; Vinicius C. da Silva; Patrícia Gomes; Caio F. R. de Oliveira; Elisângela S. Madalozzo; Edson Crusca; Raquel M. Q. Orozco; Lucas Lima; Marlon H. Cardoso; Octávio L. Franco; et al. (Probiotics and Antimicrobial Proteins, 2026)

Hyperdominant Trees Reveal Savanna Vulnerability Under Climate Change - Facundo Alvarez; Ben Hur Marimon‐Junior; Beatriz Schwantes Marimon; Wesley Jonatar Alves da Cruz; Norberto Gomes Ribeiro Júnior; Raiane Gonçalves Béu; Polyanna da Conceição Bispo; Aldair de Souza Medeiros; Glécio Machado Siqueira; Marcelo Leandro Bueno; Fabiana de Gois Aquino; Frederico Augusto Guimarães Guilherme; et al. (Global Change Biology, 2026)
The Cerrado biome, spanning ~2 million km 2 , is one of the most extensive and biodiverse tropical savannas, yet it is paradoxically dominated by only 30 hyperdominant tree species (~2% of all species, > 50% of all stems). However, their vulnerability to climate change and the effectiveness of current conservation efforts remain uncertain. By combining (i) species distribution models calibrated with edaphic‐climatic predictors and occurrence data for hyperdominant Cerrado trees with (ii) functional‐trait analyses related to ecological strategies (leaf economics, bark investment, ecophysiology, drought tolerance, regeneration, and dispersal), we identified the biomass production and reproductive traits that best predict species persistence under high‐emission scenarios (RCP8.5). Currently, only 427,980 km 2 (~17.4%) of the modeled potential environmental suitability falls within protected areas; under future climate scenarios, this protected suitable area is projected to decline by ~45.9% to 231,377 km 2 (~18.1%). This loss, resulting from land conversion with the expansion of agricultural frontiers and fire events, highlights a mismatch in current regional conservation priorities, overlooking the needs of the Cerrado and its associated biodiversity. Given ongoing land‐use change and that 58% of remaining native vegetation occurs on private lands, this mismatch highlights the urgent need to align conservation and agricultural policy. Functional trait analyses revealed a clear gradient from acquisitive “fast” to conservative “slow” strategies, reflecting trade‐offs in water‐use efficiency and biomass allocation, with leaf structural and reproductive traits best predicting species resilience to climate change. Our results indicate that a small subset of hyperdominant species not only forms current community structure but also signals the biome's resilience/vulnerability to climate change. Conservation planning should prioritize identified climate refuges and be based on functional traits to buffer the loss of functional and structural integrity in one of the world's richest and most threatened savanna ecosystems.

Encapsulation of slow-release urea in stearic acid microspheres: Effects on nutrient digestibility, nitrogen utilization, and performance in lambs - Everton C. de. Medeiros; André L. da Silva; José Morais Perreira Filho; Kevily H. de O.S. de Lucena; Gildênia A. Pereira; Mônica T. Cavalcanti; Juliana P.F. de Oliveira; Elzania S. Pereira; Edson C. Silva Filho; Leilson R. Bezerra (Animal Feed Science and Technology, 2026)

Sensitivity of lumped and semi-distributed hydrological models to 20 gridded precipitation products in a transboundary basin - Paula L. Pacheco M.; Frédéric Satgé; Marie-Paule Bonnet; Jorge Molina-Carpio; R. Pillco Zolá; Edson Ramírez; Daniel Espinoza-Romero; Renaud Hostache (Journal of Hydrology, 2025)

Differential responses of temporal interaction networks between specialist and generalist hummingbirds and native and alien plants in a Mexican cloud forest - Daniela Bravo-Galindo; Rosalba Rodríguez-Godínez; Ana I. López-Flores; Edson A. Alvarez-Alvarez; R. Carlos Almazán-Núñez (Community Ecology, 2025)

Improving current forecast by Leveraging Measured Data and numerical models via LiESNs - Felipe M. Moreno; Marcel R. de Barros; Artur Jordão; Marlon S. Mathias; Marcelo Dottori; Anna H. Reali Costa; Edson S. Gomi; Fabio G. Cozman; Eduardo A. Tannuri (Environmental Modelling & Software, 2025)

Innovative properties of sustainable galactomannans from seeds of Adenanthera pavonina, Caesalpinia pulcherrima and Delonix regia - Marcilia P. Costa; Maurycyo S. Geronço; Igor F. da S. Ramos; Monalisa de A. Lucena; Ricardo Araújo; Iluska M. Pinheiro; Rayran Walter R. de Sousa; Paulo Michel P. Ferreira; Josy A. Osajima; Manuela Amorin; Óscar Ramos; Edson C. Silva-Filho; et al. (Carbohydrate Polymers, 2025)

The tibiotarsus of a giant darter from the upper Miocene of Amazonia and weight estimates for fossil darters - Edson Guilherme; Ighor D. Mendes; Carlos D’Apolito; Lucy G. Souza; Francisco R. Negri; Kathellen G. Magalhães; Jonas P. Souza-Filho (Palaeoworld, 2025)

Management intensity does not affect the ecological indicators of coffee agroforestry systems in agricultural landscapes of the Atlantic forest zone in Brazil - Vitoria Duarte Derisso; Ricardo Gomes César; Catherine Torres de Almeida; Pedro H. S. Brancalion; Danilo R. A. Almeida; Paulo G. Molin; Aline Souza; Edson Vidal (Agroforestry Systems, 2025)

Abundance and characteristics of anthropogenic litter along the Tanzanian shores of the African Great Lakes: including volunteer involvement, outreach, and stakeholder engagement in a holistic approach - Bahati S. Mayoma; Mamlo A. Yusuph; Hellena Sailas; Zagalo Emanuel; Editrudith Lukanga; Lawrence Kitogo; Adventina A. Edson; Deogratius Simbila; Arthur Mugema; Paul Matonya; Fanuel Kasenene; Christina Sørensen; et al. (Environmental Science and Pollution Research, 2025)
Environmental pollution due to mismanaged anthropogenic litter is one of the most pressing issues facing the world today. To reduce existing environmental burdens of litter, clean-up events have increased in popularity. Here, we report on the results of the Clean Shores, Great Lakes project, in which we conducted 69 volunteer-based clean-ups along the Tanzanian shorelines of the African Great Lakes (Victoria, Tanganyika, and Nyasa (also known as Lake Malawi)). A total of 5483 volunteers engaged with the project across all clean-up sites, collecting 431,328 pieces (25,981 kg) of anthropogenic litter. Expressing the data as normalized to area (items m −2 ) or effort (items individual −1 h −1 ) revealed that the interpretation of a polluted site varies with units, highlighting the need for consistency in the field. Litter density varied from 0.06 to 13.89 items m −2 and 5.2–706 items individual −1 h −1 . Plastics were the major litter type constituting 75% of all litter (mean = 74.2 ± 12.5% across all sites), while clothing (10.9 ± 9.5%) and fishing gear (3.7 ± 5.2%) were also prevalent. Two items constituted > 40% of all collected litter, namely plastic beverage bottles (average 23.7 ± 17.1%, range 0–72.9%) and plastic bags (average 19.7 ± 13.2%, range 1–50.3%). Prioritizing intervention measures on these two items could reduce litter leakage significantly. Furthermore, a holistic approach was undertaken through voluntary engagement, citizen science involvement, stakeholder dissemination, and school visits to increase public awareness. Clean-up data when disseminated to relevant policymakers and stakeholders can motivate activity for the environmental management of anthropogenic litter and plastic pollution.

Effects of dietary supplementation with slow-release urea coated with carnauba wax on intake, ingestive behavior, selectivity, ruminal parameters, performance and carcass traits of lambs - Tainan da Silva Batista; Leilson R. Bezerra; Pedro H.S. Mazza; Analivia M. Barbosa; Beatriz S.C. de Castro; Melissa D. Ferrer; Ana Carolina Ferreira; Jasiel S. de Morais; Edson C. da Silva Filho; Ronaldo L. Oliveira (Small Ruminant Research, 2025)

Positive Feedback on Climate Warming by Stream Microbial Decomposers Indicated by a Global Space‐For‐Time Substitution Study - Javier Pérez; Luz Boyero; Richard G. Pearson; Mark O. Gessner; Alan Tonin; Naiara López‐Rojo; Juan Rubio‐Ríos; Francisco Correa‐Araneda; Alberto Alonso; Aydeé Cornejo; Ricardo J. Albariño; Sankarappan Anbalagan; et al. (Global Change Biology, 2025)
Decomposition of plant litter is a key ecological process in streams, whose contribution to the global carbon cycle is large relative to their extent on Earth. We examined the mechanisms underlying the temperature sensitivity (TS) of instream decomposition and forecast effects of climate warming on this process. Comparing data from 41 globally distributed sites, we assessed the TS of microbial and total decomposition using litter of nine plant species combined in six mixtures. Microbial decomposition conformed to the metabolic theory of ecology and its TS was consistently higher than that of total decomposition, which was higher than found previously. Litter quality influenced the difference between microbial and total decomposition, with total decomposition of more recalcitrant litter being more sensitive to temperature. Our projections suggest that (i) warming will enhance the microbial contribution to decomposition, increasing CO 2 outgassing and intensifying the warming trend, especially in colder regions; and (ii) riparian species composition will have a major influence on this process.

Viscous-cohesive fracture parameters quantification by the coupling of 3D dipole-based BEM formulation and Bayesian updating model - Luís Philipe R. Almeida; Elena Atroshchenko; Edson D. Leonel (Engineering Structures, 2025)

A hint on the unknown diversity of eastern Andes: high endemicity and new species of mammals revealed through DNA barcoding - Silvia E. Pavan; Edson F. Abreu; Pamela Y. Sánchez-Vendizú; Romina Batista; Roberta A. Murta-Fonseca; Renzo Pradel; Edgardo M. Rengifo; Mariela Leo; Víctor Pacheco; Alexandre Aleixo; Alexandre R. Percequillo; Pedro Peloso (Systematics and Biodiversity, 2024)

Structured decision-making shows broad support from diverse stakeholders for habitat conservation and restoration in Kenya’s Central Highlands - Gwili E.M. Gibbon; Martin Dallimer; Hassan Golo; Humphrey Munene; Charlene A. Wandera; Monda N. Edson; Jane C. Gachura; Tim Hobbs; Festus Ihwagi; Stephen R. Ikhamati; Samson K. Ikiara; David Kimathi; et al. (Land Use Policy, 2024)

Land use transformations in the Brazilian Savanna: A decade of soil erosion and runoff measurements - Dimaghi Schwamback; Abderraman R. Amorim Brandão; Lívia M.P. Rosalem; Paulo T.S. Oliveira; Jamil A.A. Anache; Edson Wendland; Ronny Berndtsson; Magnus Persson (CATENA, 2024)

Corrigendum: Ocean surface radiation measurement best practices - Laura D. Riihimaki; Meghan F. Cronin; Raja Acharya; Nathan Anderson; John A. Augustine; Kelly A. Balmes; Patrick Berk; Roberto Bozzano; Anthony Bucholtz; Kenneth J. Connell; Christopher J. Cox; Alcide G. di Sarra; et al. (Frontiers in Marine Science, 2024)

Gene flow, mating patterns and inbreeding depression in Roupala montana var. brasiliensis, a neotropical timber species - Fernanda B. Pereira; Alexandre M. Sebbenn; David H. Boshier; Bruno C. Rossini; Celso L. Marino; Miguel L. M. Freitas; João R. B. F. Rosa; Edson Vidal; Evandro V. Tambarussi (New Forests, 2024)

Ocean surface radiation measurement best practices - Laura D. Riihimaki; Meghan F. Cronin; Raja Acharya; Nathan Anderson; John A. Augustine; Kelly A. Balmes; Patrick Berk; Roberto Bozzano; Anthony Bucholtz; Kenneth J. Connell; Christopher J. Cox; Alcide G. di Sarra; et al. (Frontiers in Marine Science, 2024)
Ocean surface radiation measurement best practices have been developed as a first step to support the interoperability of radiation measurements across multiple ocean platforms and between land and ocean networks. This document describes the consensus by a working group of radiation measurement experts from land, ocean, and aircraft communities. The scope was limited to broadband shortwave (solar) and longwave (terrestrial infrared) surface irradiance measurements for quantification of the surface radiation budget. Best practices for spectral measurements for biological purposes like photosynthetically active radiation and ocean color are only mentioned briefly to motivate future interactions between the physical surface flux and biological radiation measurement communities. Topics discussed in these best practices include instrument selection, handling of sensors and installation, data quality monitoring, data processing, and calibration. It is recognized that platform and resource limitations may prohibit incorporating all best practices into all measurements and that spatial coverage is also an important motivator for expanding current networks. Thus, one of the key recommendations is to perform interoperability experiments that can help quantify the uncertainty of different practices and lay the groundwork for a multi-tiered global network with a mix of high-accuracy reference stations and lower-cost platforms and practices that can fill in spatial gaps.

The convergence approach may be critical to improving early situational awareness in hostile radioactive environments - Vitor W.L. Silva; William H.S. Profeta; Rodrigo C. Curzio; Avelino Santos; Tercio Brum; Edson R. Andrade (Journal of Environmental Radioactivity, 2024)

Slow-releasing urea coated with low-trans vegetable lipids: Effects on lamb performance, nutrient digestibility, nitrogen balance, and blood parameters - Kevily H. de O.S. de Lucena; Pedro H.S. Mazza; Ronaldo L. Oliveira; Analivia M. Barbosa; José M. Perreira Filho; Rui J.B. Bessa; Susana P. Alves; Ricardo L. Edvan; Elzania S. Pereira; Mozart Fonseca; Edson C. Silva Filho; Leilson R. Bezerra (Animal Feed Science and Technology, 2024)

Lost life expectancy following a hypothetical urban radiological incident - Suzana C.T. Neves; Luis R.P. Horta; Rodrigo V. Machado; Danielle E.G. Furuya; Pollyana S. Shimada; Alba R.A. Arana; Ana Paula A. Favareto; Edson R. Andrade (Journal of Environmental Radioactivity, 2024)

Nitrogen Losses in Field Irrigated with Domestic Sewage Through Subsurface Drip Irrigation for Sugarcane in Brazil - Eduardo A. A. Barbosa; Ivo Z. Gonçalves; Edson E. Matsura; Daniel R. C. Feitosa; Natália F. Tuta; Leonardo N. S. Santos; Aline A. Nazario; Fábio R. Marin (Sugar Tech, 2023)

Essential oil in bentonite: Effect of organofunctionalization on antibacterial activities - Luís H. Oliveira; Idglan S. de Lima; Enedina R. da S. Neta; Sidney G. de Lima; Pollyana Trigueiro; Josy A. Osajima; Edson C. da Silva-Filho; Maguy Jaber; Maria G. Fonseca (Applied Clay Science, 2023)

Four new species of Anenterotrema Stunkard, 1938 (Digenea: Dicrocoellidae) infecting phyllostomid bats in the Peruvian Amazon - Edson R. Cacique; Raúl Bello; Hugo Zamora; Katherin Mares; Gloria Saéz; Ruperto Severino; Celso Cruces; Jhon D. Chero (Systematic Parasitology, 2023)

Nereididae (Annelida) phylogeny based on molecular data - Paulo R. Alves; Kenneth M. Halanych; Edson P. Silva; Cinthya S. G. Santos (Organisms Diversity & Evolution, 2023)

Antifungal potential of aqueous extracts of coconut (Cocos nucifera L.) by-products against blue mold disease on Persian lime during storage - Edson J. Hernández-Flores; Francisco J. Blancas-Benitez; Beatriz Montaño-Leyva; Ramsés R. González-Estrada (Food Control, 2023)

Environmental surveillance detects circulating vaccine-derived poliovirus type 2 that was undetected by acute flaccid paralysis surveillance in 2021 in Uganda - Phionah Tushabe; Josephine Bwogi; James Peter Eliku; Francis Aine; Molly Birungi; Joseph Gaizi; Lucy Nakabazzi; Theopista Kabaliisa; Irene Turyahabwe; Prossy Namuwulya; Mary Bridget Nanteza; Henry Bukenya; et al. (Archives of Virology, 2023)
The success of the global polio eradication initiative is threatened by the genetic instability of the oral polio vaccine, which can result in the emergence of pathogenic vaccine-derived polioviruses following prolonged replication in the guts of individuals with primary immune deficiencies or in communities with low vaccination coverage. Through environmental surveillance, circulating vaccine-derived poliovirus type 2 was detected in Uganda in the absence of detection by acute flaccid paralysis (AFP) surveillance. This underscores the sensitivity of environmental surveillance and emphasizes its usefulness in supplementing AFP surveillance for poliovirus infections in the race towards global polio eradication.

Exploring the use of Sentinel-2 datasets and environmental variables to model wheat crop yield in smallholder arid and semi-arid farming systems - Sarchil Hama Qader; Chigozie Edson Utazi; Rhorom Priyatikanto; Peshawa Najmaddin; Emad Omer Hama-Ali; Nabaz R. Khwarahm; Andrew J. Tatem; Jadu Dash (Science of The Total Environment, 2023)

Pretreated banana peels as a source for the recovery of phenolic compounds: Extraction kinetics, ultrasound optimization, and conventional extraction methods - Suian J. Granella; Taise R. Bechlin; Divair Christ; Silvia R. Coelho Machado; Carina C. Triques; Edson A. da Silva (Journal of Applied Research on Medicinal and Aromatic Plants, 2023)

Invasive Aspergillosis in Patients with Acute Leukemia: Comparison Between Acute Myeloid and Acute Lymphoid Leukemia - Arnaldo L. Colombo; Maria Daniela Bergamasco; Simone A. Nouér; Paulo de Tarso Oliveira e Castro; Alessandro C. Pasqualotto; Flavio de Queiroz-Telles; Edson Abdala; Jessica F. Ramos; Diego R. Falci; Marcio Nucci (Mycopathologia, 2023)

Oxidized cellulose nanofibers from sugarcane bagasse obtained by microfluidization: Morphology and rheological behavior - Cibele Carneiro Pessan; Juliana Silva Bernardes; Sílvia H.P. Bettini; Edson R. Leite (Carbohydrate Polymers, 2023)

Radon and thoron concentrations in the southwest region of Angola: dose assessment and implications for risk mapping - Edson Baptista; Alcides J. S. C. Pereira; Filipa P. Domingos; Sérgio L. R. Sêco (Environmental Geochemistry and Health, 2023)

Soil Penetration Resistance and Sugarcane Rooting Under Subsuperficial Drip Irrigation Levels - Ronaldo S. Resende; Fernando L. D. Cintra; Edson Patto Pacheco; Júlio R. A. de Amorim; Renata S. B. Gomes; Sandra M. da Silva (Sugar Tech, 2023)
Knowledge of the soil water regime in a dynamic equilibrium condition (steady state) of the emitter–soil–plant system is essential to evaluate the adopted irrigation management, aiming to maximize the water use efficiency in irrigation. Thus, our objective was to determine the integrated effect of four irrigation levels on the soil moisture (θ v ) distribution pattern, mechanical soil penetration resistance (PR), and sugarcane rooting. Irrigation levels were established based on the percentage of reference evapotranspiration (ETo), as follows: 40% (W1), 70% (W2), 100% (W3), and 130% (W4) of ETo. From the soil moisture profile and PR versus θ v regression models, PR profiles for each irrigation level were estimated. At the end of the crop cycle, trenches were opened to assess sugarcane root system. According to the results, the water dynamic in the soil profile resulted in a soil-wetting pattern that did not match the sugarcane rooting profile. For treatments W3 and W4 the wetting pattern indicated water loss through deep percolation. For all treatments and considering the entire soil profile, the PR values ranged from < 2 to 10 MPa. Also, the roots were superficially spread and limited to the first 0.35 m in depth for all irrigation depths applied. Although the soil wetting by irrigation reduced the strength of the cohesive layer, this reduction was insufficient to allow the deepening of plant roots. The su garcane root development was limited to the region of the soil profile defined by a PR value approximately equal to 2.0 MPa.

Improved remediation of contaminated water using ZnO systems via chemical treatment: applications, implications and toxicological mitigation - Josy A. Osajima; Alexandro S. Sá; Rodrigo P. Feitosa; Marcelo B. Furtini; Luzia M. C. Honorio; Maria G. Fonseca; Pollyana Trigueiro; Paula Caregnato; Eduardo R. Triboni; Edson C. Silva-Filho (Sustainable Water Resources Management, 2023)

Bradyrhizobium occurrence in nodules of perennial horsegram - Mayan Blanc Amaral; Tamiris dos Santos Lopes; Caroline Bueno Feder; Thiago Gonçalves Ribeiro; Rafael Sanches Pacheco; Thiago Neves Teixeira; Edevaldo de Castro Monteiro; Israel Oliveira Ramalho; Robert de O. Macedo; Robert M. Boddey; Jerri Edson Zilli; Bruno J. R. Alves (Brazilian Journal of Microbiology, 2022)

Integrative Taxonomy Reveals a Panmictic Population of Henneguya longisporoplasma n. sp. (Cnidaria: Myxozoa) in the Amazon Basin - Suellen A. Zatti; Amanda M. R. Marinho; Edson A. Adriano; Antônio A. M. Maia (Acta Parasitologica, 2022)

Edaphic factors as genetic selection agents and adaptation drivers of native plant species in harsh environments of the Brazilian savanna - Leide R. M. Andrade; Fabiana G. Aquino; Guillaume Echevarria; Jamile S. Oliveira; Cícero D. Pereira; Juaci V. Malaquias; Karina S. Souza; Emmanuelle Montargès-Pelletier; Fábio G. Faleiro; Fábio B. Reis Junior; Zenilton G. Miranda; Edson E. Sano; et al. (Plant and Soil, 2022)

Conversion of rice husk into reducing sugars: influence of pretreatment with water and [C16MIM][Br−] ionic liquid - Patrícia D. Bohn; Chayene G. Anchieta; Kátia R. Kuhn; Edson I. Muller; Flávio D. Mayer; Raquel C. Kuhn (Clean Technologies and Environmental Policy, 2022)

Defense response-like reaction associated with an anomaly in Eucalyptus grandis - Maria C. P. Fuchs; Bruno C. Rossini; Marcio L. Acencio; Ney Lemke; Esteban R. González; Salvatore Moricca; Tiziana Panzavolta; Edson L. Furtado; Shinitiro Oda; Celso L. Marino (Trees, 2022)

Correction to: Search for reservoirs of ‘Candidatus Liberibacter solanacearum’ and mollicutes in weeds associated with carrot and celery crops - Ana Alfaro-Fernández; Mercedes Verdeguer; Francisco Rodríguez-León; Isabel Ibáñez; Desamparados Hernández; Gabriela R. Teresani; Edson Bertolini; Mariano Cambra; María Isabel Font (European Journal of Plant Pathology, 2022)

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

Psidium myrtoides O. Berg fruit and leaves: physicochemical characteristics, antifungal activity and chemical composition of their essential oils in different seasons - Alline L. B. Dias; Hellen R. F. Batista; Wendel C. Sousa; Elisa F. L. C. Bailão; Jamira D. Rocha; Eugenio M. Sperandio; Cassia C. Fernandes; Edson L. Souchie; Mayker L. D. Miranda (Natural Product Research, 2022)

Unlocking the history of a trans‐Atlantic invader: Did the human slave trade impact Brown mussel dispersal? - Sávio H. Calazans; Carla R. Lourenço; Katy R. Nicastro; Claudia H. Tagliaro; Gerardo I. Zardi; Carlos E. L. Ferreira; Flavio da C. Fernandes; Edson P. Silva; Eric A. Hoffman (Journal of Biogeography, 2021)
Aim Brown mussels exhibit a trans‐Atlantic distribution putatively caused by either native dispersal or artificial gene flow, likely in concert with the transport of enslaved people from Africa. Evolutionary history and demographic models of this widespread species may clarify how the present‐day distribution was impacted by natural versus artificial dispersal. Particularly, dating the timing of the South American/African split may determine whether the human slave trade likely impacted the contemporary distribution of brown mussels. Location Coastal Brazil, Morocco, South Africa, and Mozambique. Taxon Perna perna (Linnaeus 1758). Methods We genotyped a total of 644 samples from 18 populations at 10 microsatellite loci. We estimated genetic structure with clustering algorithms in STRUCTURE and GENETIX. We estimated genetic distances by characterizing patterns of pair‐wise F ST using the program FSTAT, evaluating differences among and between regions via AMOVA, and testing isolation by distance in IBDWS. To estimate and date the most likely pathway by which P . perna crossed the Atlantic Ocean we used Bayesian factors from thermodynamically heated coalescent simulations in the program MIGRATE‐n. Results We found no general pattern of reduced or elevated levels of genetic diversity within any region across site or locus. We identified four genetic clusters: East South Africa (ESA), West South Africa (WSA), Brazil (BR) and North Africa (MO); F ST ranged from 0.06 to 0.11 among regions and exhibited a significant pattern of isolation by distance. Migration models indicated that P . perna dispersed from WSA to MO and from there to BR of approximately 2,000 years. Main conclusions Multiple lines of evidence suggest the Brazilian populations of P . perna have been a long‐standing native population, originating from northern Africa and are unlikely a consequence of the African slave trade. Although, human introduction cannot be ruled out South American P . perna populations exhibited genetic characteristics indicative of a divergent, isolated and established population, featuring the genetic signature expected for a native population.

Phenoxyacetohydrazones against Trypanosoma cruzi - Camila Capelini; Kátia R. de Souza; Juliana M. C. Barbosa; Kelly Salomão; Policarpo A. Sales Junior; Silvane M. F. Murta; Solange M. S. V. Wardell; James L. Wardell; Edson F. da Silva; Samir A. Carvalho (Medicinal Chemistry Research, 2021)

Sepsis in cougar (Puma concolor) associated with Chromobacterium violaceum - Mayara C. S. R. Mesquita; Janaina Marcela A. R. Moreira; Beatriz S. Nogueira; Thais Morgado; Marlon Ribeiro; Edson Moleta Colodel; Luciano Nakazato; Valéria Dutra (Brazilian Journal of Microbiology, 2021)

Asymmetric effects of changes in the habitat‐forming algae Sargassum on different associated mobile faunas along São Paulo coast, Brazil - Fosca P. P. Leite; Claudia Bottcher; Ilana D. A. Lewinsohn; Silvana G. L. Siqueira; Karine F. R. Mansur; Pedro A. S. Longo; Edson A. Vieira (Marine Ecology, 2021)
Macroalgae constitute an important habitat for several marine invertebrates, and their biomass and structural complexity modulates the abundance and diversity of species that live on them. Overall, fluctuations in algae biomass inflict fluctuations in the abundance of the associated mobile macrofauna, but the structure of the community may vary according to how each group/species uses the resources provided by the algal habitat. Here, we evaluated how temporal variations in the biomass of Sargassum algal bed (increase, decrease, or maintenance) can affect the abundance, density, and assemblage structure of distinct associated faunistic groups. The collections were performed in three rocky shores located on the north coast of São Paulo, southeastern Brazil, during Fall and Spring. We observed different patterns of algal substrate variation between sampling events, and this reflected on variable effects on the associated fauna. The algal substrate reduction was accompanied by the reduction in the abundance and density of all associated faunal groups. However, the increase or maintenance of the algal substrate was accompanied by an increase in the abundance of peracarids, due to the dominance of herbivorous species, while other taxonomic groups like mollusks and polychaetes decreased or maintained their abundance, although with higher species evenness of gastropods when alga increases. Seasonal biomass variations in macroalgae beds are relevant for the dynamics of its associated fauna, and our results indicate that some taxonomic groups may preferentially use the available extra resources originated from biomass increment when compared to other groups.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

The big picture of field hydrology studies in Brazil - Davi C. D. Melo; Jamil A. A. Anache; Cristiano das N. Almeida; Jaqueline V. Coutinho; Geraldo M. Ramos Filho; Lívia M. P. Rosalem; Natália S. Pelinson; Guilherme L. R. A. Ferreira; Dimaghi Schwamback; Kalyl G. Calixto; João P. G. Siqueira; Jean C. Duarte-Carvajalino; et al. (Hydrological Sciences Journal, 2020)

An unusual bidentate methionine ruthenium(II) complex: photo-uncaging and antimicrobial activity - Aurideia P. de Sousa; Ana C. S. Gondim; Eduardo H. S. Sousa; Mayron A. de Vasconcelos; Edson H. Teixeira; Beatriz Pinheiro Bezerra; Alejandro Pedro Ayala; Patrícia H. R. Martins; Luiz Gonzaga de França Lopes; Alda K. M. Holanda (JBIC Journal of Biological Inorganic Chemistry, 2020)

Tree diversity and above-ground biomass in the South America Cerrado biome and their conservation implications - Paulo S. Morandi; Beatriz Schwantes Marimon; Ben Hur Marimon-Junior; James A. Ratter; Ted R. Feldpausch; Guarino Rinaldi Colli; Cássia Beatriz Rodrigues Munhoz; Manoel Cláudio da Silva Júnior; Edson de Souza Lima; Ricardo Flores Haidar; Luzmila Arroyo; Alejandro Araujo Murakami; et al. (Biodiversity and Conservation, 2020)

Evidence for positive allosteric modulation of cognitive-enhancing effects of nicotine in healthy human subjects - Britta Hahn; Megan E. Shrieves; Cory K. Olmstead; Marie B. Yuille; Joshua J. Chiappelli; Edna F. R. Pereira; Edson X. Albuquerque; William P. Fawcett (Psychopharmacology, 2020)
Rationale Cognitive benefits of nicotinic acetylcholine receptor (nAChR) agonists are well established but have generally been of small magnitude and uncertain clinical significance. A way of raising the effect size may be to facilitate agonist-induced responses by co-administering a nAChR positive allosteric modulator (PAM). Objective The aim was to test whether galantamine, a PAM at several nAChR subtypes, can potentiate the cognitive-enhancing effects of nicotine. Methods Twenty-six adult never-smokers were treated, in a double-blind counterbalanced sequence, with nicotine (7 mg/24 h, transdermally) and galantamine (4 mg, p.o.) combined, nicotine alone, galantamine alone, and double placebo. A low dose of galantamine was chosen to minimize acetylcholinesterase inhibition, which was verified in blood assays. In each condition, participants were tested with three cognitive tasks. Results Nicotine significantly improved reaction time (RT) and signal detection in a visuospatial attention task and the Rapid Visual Information Processing Task. Galantamine did not modulate these effects. A trend toward RT reduction by galantamine correlated with acetylcholinesterase inhibition. In a change detection task, there were no effects of nicotine or galantamine alone on accuracy or RT. However, both drugs combined acted synergistically to reduce RT. This effect was not associated with acetylcholinesterase inhibition. Conclusions A pattern consistent with allosteric potentiation of nicotine effects by galantamine was observed on one of six performance measures. This may reflect specific nAChR subtype involvement, or additional pharmacological actions of galantamine may have overshadowed similar interactions on other measures. The finding suggests that allosteric potentiation of nAChR agonist-induced cognitive benefits is possible in principle.

Volatiles released by damaged leaves of Piper mollicomum (Piperaceae) act as cues for predaceous wasps: evidence using plasticine dummies as herbivore model - Edson A. Vieira; Rafael Arruda; Kamila F. Massuda; Poliana Cardoso-Gustavson; Elsie F. Guimarães; José R. Trigo (Arthropod-Plant Interactions, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Antioxidant activity of three seaweeds from tropical reefs of Brazil: potential sources for bioprospecting - Juliane B. Vasconcelos; Edson R. T. P. P. de Vasconcelos; Vanessa Urrea-Victoria; Patrícia S. Bezerra; Thiago N. V. Reis; Adilma L. M. Cocentino; Daniela M. A. F. Navarro; Fungyi Chow; Arsenio J. Areces; Mutue T. Fujii (Journal of Applied Phycology, 2019)

Biosorption of nickel(II) and copper(II) ions from synthetic and real effluents by alginate-based biosorbent produced from seaweed Sargassum sp. - Carlos E. R. Barquilha; Eneida S. Cossich; Célia R. G. Tavares; Edson A. da Silva (Environmental Science and Pollution Research, 2019)

Development of Transgenic Sugarcane Resistant to Sugarcane Borer - Plinio T. Cristofoletti; Edson L. Kemper; Adriana N. Capella; Sandra R. Carmago; Juliana L. Cazoto; Fernanda Ferrari; Tederson L. Galvan; Luciane Gauer; Gustavo A. Monge; Marcelo A. Nishikawa; Nicolas Z. Santos; Altair A. Semeao; et al. (Tropical Plant Biology, 2018)

Characterization of resistance to the bean weevil Acanthoscelides obtectus Say, 1831 (Coleoptera: Bruchidae) in common bean genotypes - Edson L. L. Baldin; Fernando M. Lara; Roberto S. Camargo; Luiz E. R. Pannuti (Arthropod-Plant Interactions, 2017)

Brain injury after moderate drowning: subtle alterations detected by functional magnetic resonance imaging - Mariana P. Nucci; Katerina Lukasova; João R. Sato; Edson Amaro (Brain Imaging and Behavior, 2017)

Effect of coupling noise on the interpretation of results of electromagnetic horizontal sounding and modeling - Leonardo S. R. Mocitaiba; Edson E. S. Sampaio; Olivar A. L. de Lima (Studia Geophysica et Geodaetica, 2017)

Remediation of Phenanthrene-Contaminated Soil by Persulfate Activated with Fe-Modified Diatomite: Kinetic and Statistical Approaches - Celyna K. O. Silva-Rackov; Leandro G. Aguiar; Alessandra R. Souza; Silvia S. O. Silva; Alan G. Câmara; Marilda M. G. R. Vianna; Edson L. Foletto; Claudio A. O. Nascimento; Osvaldo Chiavone-Filho (Water, Air, & Soil Pollution, 2017)

Atlantic small‐mammal: a dataset of communities of rodents and marsupials of the Atlantic forests of South America - Ricardo S. Bovendorp; Nacho Villar; Edson F. de Abreu‐Junior; Carolina Bello; André L. Regolin; Alexandre R. Percequillo; Mauro Galetti (Ecology, 2017)
The contribution of small mammal ecology to the understanding of macroecological patterns of biodiversity, population dynamics, and community assembly has been hindered by the absence of large datasets of small mammal communities from tropical regions. Here we compile the largest dataset of inventories of small mammal communities for the Neotropical region. The dataset reviews small mammal communities from the Atlantic forest of South America, one of the regions with the highest diversity of small mammals and a global biodiversity hotspot, though currently covering less than 12% of its original area due to anthropogenic pressures. The dataset comprises 136 references from 300 locations covering seven vegetation types of tropical and subtropical Atlantic forests of South America, and presents data on species composition, richness, and relative abundance (captures/trap‐nights). One paper was published more than 70 yr ago, but 80% of them were published after 2000. The dataset comprises 53,518 individuals of 124 species of small mammals, including 30 species of marsupials and 94 species of rodents. Species richness averaged 8.2 species (1–21) per site. Only two species occurred in more than 50% of the sites (the common opossum, Didelphis aurita and black‐footed pigmy rice rat Oligoryzomys nigripes ). Mean species abundance varied 430‐fold, from 4.3 to 0.01 individuals/trap‐night. The dataset also revealed a hyper‐dominance of 22 species that comprised 78.29% of all individuals captured, with only seven species representing 44% of all captures. The information contained on this dataset can be applied in the study of macroecological patterns of biodiversity, communities, and populations, but also to evaluate the ecological consequences of fragmentation and defaunation, and predict disease outbreaks, trophic interactions and community dynamics in this biodiversity hotspot.

Range shifts or extinction? Ancient DNA and distribution modelling reveal past and future responses to climate warming in cold‐adapted birds - Vendela K. Lagerholm; Edson Sandoval‐Castellanos; Amélie Vaniscotte; Olga R. Potapova; Teresa Tomek; Zbigniew M. Bochenski; Paul Shepherd; Nick Barton; ‎Marie‐Claire Van Dyck; Rebecca Miller; ‎Jacob Höglund; Nigel G. Yoccoz; et al. (Global Change Biology, 2017)
Global warming is predicted to cause substantial habitat rearrangements, with the most severe effects expected to occur in high‐latitude biomes. However, one major uncertainty is whether species will be able to shift their ranges to keep pace with climate‐driven environmental changes. Many recent studies on mammals have shown that past range contractions have been associated with local extinctions rather than survival by habitat tracking. Here, we have used an interdisciplinary approach that combines ancient DNA techniques, coalescent simulations and species distribution modelling, to investigate how two common cold‐adapted bird species, willow and rock ptarmigan ( Lagopus lagopus and Lagopus muta ), respond to long‐term climate warming. Contrary to previous findings in mammals, we demonstrate a genetic continuity in Europe over the last 20 millennia. Results from back‐casted species distribution models suggest that this continuity may have been facilitated by uninterrupted habitat availability and potentially also the greater dispersal ability of birds. However, our predictions show that in the near future, some isolated regions will have little suitable habitat left, implying a future decrease in local populations at a scale unprecedented since the last glacial maximum.

Search for reservoirs of ‘Candidatus Liberibacter solanacearum’ and mollicutes in weeds associated with carrot and celery crops - Ana Alfaro-Fernández; Mercedes Verdeguer; Francisco Rodríguez-León; Isabel Ibáñez; Desamparados Hernández; Gabriela R. Teresani; Edson Bertolini; Mariano Cambra; María Isabel Font (European Journal of Plant Pathology, 2017)

“Burnout in Medical Oncology Fellows: a Prospective Multicenter Cohort Study in Brazilian Institutions” - Daniel I. G. Cubero; Renata Rego Lins Fumis; Thiago Hérick de Sá; Aldo Dettino; Felipe Osório Costa; Brigitte M. R. H. Adam Van Eyll; Carlos Beato; Fernanda Maris Peria; Augusto Mota; José Altino; Sérgio Jobim Azevedo; Duílio Reis da Rocha Filho; et al. (Journal of Cancer Education, 2016)

The mechanism by which P250L mutation impairs flavivirus-NS1 dimerization: an investigation based on molecular dynamics simulations - Edson R. A. Oliveira; Ricardo B. de Alencastro; Bruno A. C. Horta (European Biophysics Journal, 2016)

Hydrologic Simulation for Water Balance Improvement in an Outcrop Area of the Guarani Aquifer System - Aline R. Machado; Edson Wendland; Peter Krause (Environmental Processes, 2016)

Optimizing Phenanthrene and Anthracene Oxidation by Sodium Persulfate and Fe-Modified Diatomite Using the Response Surface Method - Celyna K. O. da Silva; Marilda M. G. R. Vianna; Edson L. Foletto; Osvaldo Chiavone-Filho; Claudio A. O. do Nascimento (Water, Air, & Soil Pollution, 2015)

Species richness and areas of endemism of oryzomyine rodents (Cricetidae, Sigmodontinae) in South America: an ndm / vndm approach - Joyce R. do Prado; Pamella G. G. Brennand; Leandro P. Godoy; Gustavo S. Libardi; Edson F. de Abreu‐Júnior; Paulo R. O. Roth; Elisandra A. Chiquito; Alexandre R. Percequillo (Journal of Biogeography, 2015)
Aim To infer areas of endemism for the tribe Oryzomyini in South America by employing a database of species richness and geographical distribution, and to compare these results with areas of endemism and species richness proposed in the literature for other taxa. Location We analysed specimens of the tribe Oryzomyini distributed throughout South and Central America, which are housed in European, North and South American museums and collections. Methods We analysed 2768 occurrence records for 102 species of the tribe Oryzomyini using the ndm / vndm algorithm and three different grid sizes to assess the possible effects of grid cell area on the results. Results Using the overlap of consensus areas in South America, we identified three generalized areas of endemism for the Oryzomyini: north‐western South America ( NWSA ), eastern South American ( ESA ), and northern South America ( NSA ); we also identified the Galápagos archipelago ( GA ) as an area of endemism. Main conclusions Areas of endemism detected in the continental portion of South America include its three main mountain chains: the Andes Cordillera, the Guyanan Shields, and an area east of the Brazilian Shield named Serra do Mar. Each of these regions encompasses many different types of vegetation, and the species richness and composition of the areas of endemism of the tribe are directly related to this environmental diversity. Different grid sizes affected the distributional heterogeneity of the consensus areas. The smallest grid cell size identified mainly Andean areas, which contain a higher number of more exclusive species in a small area along a steep elevational gradient. In contrast, the largest grid size identified areas of endemism along an environmental gradient that co‐varied with latitude and longitude. The identified areas of endemism are corroborated by previous studies on other taxa.

Interaction of brain areas of visual and vestibular simultaneous activity with fMRI - Hellen M. Della-Justina; Humberto R. Gamba; Katerina Lukasova; Mariana P. Nucci-da-Silva; Anderson M. Winkler; Edson Amaro (Experimental Brain Research, 2015)

The spectral changes of deforestation in the Brazilian tropical savanna - Ralph Trancoso; Edson E. Sano; Paulo R. Meneses (Environmental Monitoring and Assessment, 2015)

Advances in Air–Sea $$\hbox {CO}_2$$ CO 2 Flux Measurement by Eddy Correlation - Byron W. Blomquist; Barry J. Huebert; Christopher W. Fairall; Ludovic Bariteau; James B. Edson; Jeffrey E. Hare; Wade R. McGillis (Boundary-Layer Meteorology, 2014)

On the origin of the N orwegian lemming - Vendela K. Lagerholm; Edson Sandoval‐Castellanos; Dorothee Ehrich; Natalia I. Abramson; Adam Nadachowski; Daniela C. Kalthoff; Mietje Germonpré; Anders Angerbjörn; John R. Stewart; Love Dalén (Molecular Ecology, 2014)
The Pleistocene glacial cycles resulted in significant changes in species distributions, and it has been discussed whether this caused increased rates of population divergence and speciation. One species that is likely to have evolved during the Pleistocene is the Norwegian lemming ( L emmus lemmus ). However, the origin of this species, both in terms of when and from what ancestral taxon it evolved, has been difficult to ascertain. Here, we use ancient DNA recovered from lemming remains from a series of Late Pleistocene and Holocene sites to explore the species' evolutionary history. The results revealed considerable genetic differentiation between glacial and contemporary samples. Moreover, the analyses provided strong support for a divergence time prior to the Last Glacial Maximum ( LGM ), therefore likely ruling out a postglacial colonization of Scandinavia. Consequently, it appears that the Norwegian lemming evolved from a small population that survived the LGM in an ice‐free Scandinavian refugium.

Mauritic acid: a new dammarane triterpene from the roots of Mauritia flexuosa L.f. (Arecaceae) - Hector H.F. Koolen; Elzalina R. Soares; Felipe M.A. da Silva; Aimêe A. de Oliveira; Antonia Q.L. de Souza; Lívia S. de Medeiros; Edson Rodrigues-Filho; Bruno C. Cavalcanti; Cláudia O. Pessoa; Manoel O. Moraes; Marcos J. Salvador; Afonso D.L. de Souza (Natural Product Research, 2013)

Wind tunnel study of turbulent flow past an urban canyon model - Edson R. Marciotto; Gilberto Fisch (Environmental Fluid Mechanics, 2013)

Ferritin-like family proteins in the anaerobe Bacteroides fragilis: when an oxygen storm is coming, take your iron to the shelter - Edson R. Rocha; C. Jeffrey Smith (BioMetals, 2013)

Variability of energy fluxes in relation to the net-radiation of urban and suburban areas: a case study - Edson R. Marciotto (Meteorology and Atmospheric Physics, 2013)

The Role of the Eu3+ Concentration on the SrMoO4:Eu Phosphor Properties: Synthesis, Characterization and Photophysical Studies - Ana Paula A. Marques; Marcos Takashi S. Tanaka; Elson Longo; Edson R. Leite; Ieda Lucia Viana Rosa (Journal of Fluorescence, 2011)

The Astrocyte-Derived α7 Nicotinic Receptor Antagonist Kynurenic Acid Controls Extracellular Glutamate Levels in the Prefrontal Cortex - Hui-Qiu Wu; Edna F. R. Pereira; John P. Bruno; Roberto Pellicciari; Edson X. Albuquerque; Robert Schwarcz (Journal of Molecular Neuroscience, 2010)

Molecular and Cellular Actions of Galantamine: Clinical Implications for Treatment of Organophosphorus Poisoning - Edna F. R. Pereira; Yasco Aracava; Manickavasagom Alkondon; Miriam Akkerman; Istvan Merchenthaler; Edson X. Albuquerque (Journal of Molecular Neuroscience, 2010)

Management of melon bacterial blotch by plant beneficial bacteria - Flávio H. V. Medeiros; Iale S. F. Moraes; Edson B. da Silva Neto; Elineide B. Silveira; Rosa de Lima R. Mariano (Phytoparasitica, 2009)

Kinetics of Lead Bioaccumulation from a Hydroponic Medium by Aquatic Macrophytes Pistia stratiotes - Fernando R. Espinoza-Quiñones; Aparecido N. Módenes; Ismael L. Costa; Soraya M. Palácio; Nayara Szymanski; Daniela E. G. Trigueros; Alexander Dimitrov Kroumov; Edson A. Silva (Water, Air, & Soil Pollution, 2009)

Lectin extracted from Canavalia grandiflora seeds presents potential anti-inflammatory and analgesic effects - Breno S. Nunes; Nathalie S. Rensonnet; Daniela Dal-Secco; Silvio M. Vieira; Benildo S. Cavada; Edson H. Teixeira; Tales R. Moura; Cícero S. Teixeira; Juliana T. Clemente-Napimoga; Fernando Q. Cunha; Marcelo H. Napimoga (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

Europium(III) Concentration Effect on the Spectroscopic and Photoluminescent Properties of BaMoO4:Eu - Ieda L. V. Rosa; Ana Paula A. Marques; Marcos T. S. Tanaka; Fabiana V. Motta; José A. Varela; Edson R. Leite; Elson Longo (Journal of Fluorescence, 2009)

Sensors for physical fluxes at the sea surface: energy, heat, water, salt - R. A. Weller; E. F. Bradley; J. B. Edson; C. W. Fairall; I. Brooks; M. J. Yelland; R. W. Pascal (Ocean Science, 2008)
The current status of meteorological sensors used aboard ships and buoys to measure the air-sea fluxes of momentum, heat, and freshwater is reviewed. Methods of flux measurement by the bulk aerodynamic, inertial dissipation and eddy-correlation methods are considered; and areas are identified where improvements are needed in measurement of the basic variables. In some cases, what is required is the transition from emergent to operational technology, in others new technologies are needed. Uncertainties in measured winds caused by flow distortion over the ship are discussed; and the possible role of computational fluid mechanics models to obtain corrections is considered. Basic studies are also needed on the influence of waves and rain on the fluxes. The issues involved in the specification of sea surface temperature are described, and the relative merits of the available sensors are discussed. The improved capability of buoy-mounted systems will depend on the emergence of low-power instruments, and/or new means of increasing the available power capacity. Other issues covered include the continuing uncertainty about the performance of rain gauges and short-wave radiometers. Also, the requirements for new instruments to extend the range of observations to extreme wind conditions are outlined, and the latest developments in the measurement of aerosol fluxes by eddy-correlation are presented.

SiO2–GeO2 Soot Preform as a Core for Eu2O3 Nanocoating: Synthesis and Photophysical Study - Ieda L. V. Rosa; Larissa H. Oliveira; Carlos K. Suzuki; José A. Varela; Edson R. Leite; Elson Longo (Journal of Fluorescence, 2008)

Synthesis, Characterization and Photophysical Properties of Eu3+ Doped in BaMoO4 - Ieda L. V. Rosa; Ana Paula A. Marques; Marcos T. S. Tanaka; Dulce M. A. Melo; Edson R. Leite; Elson Longo; José Arana Varela (Journal of Fluorescence, 2008)

Effect of the Order and Disorder of BaMoO4 Powders in Photoluminescent Properties - Ana Paula A. Marques; Francini C. Picon; Dulce M. A. Melo; Paulo S. Pizani; Edson R. Leite; José A. Varela; Elson Longo (Journal of Fluorescence, 2008)

Acetogenins in Annona muricata L. (annonaceae) leaves are potent molluscicides - J. De S. Luna; J. M. De Carvalho; M. R. F. De Lima; L. W. Bieber; Edson De S. Bento; X. Franck; A. E. G. Sant’ana (Natural Product Research, 2006)

Impact of foraging byMonochamus titillator [Col.: Cerambycidae] on within-tree populations ofDendroctonus frontalis [Col.: Scolytidae] - R. N. Coulson; Don N. Pope; J. A. Gagne; W. Scott Fargo; P. E. Pulley; L. J. Edson; T. L. Wagner (BioControl, 1980)